2023
DOI: 10.1186/s12974-023-02923-6
|View full text |Cite
|
Sign up to set email alerts
|

ASK1-K716R reduces neuroinflammation and white matter injury via preserving blood–brain barrier integrity after traumatic brain injury

Shan Meng,
Hui Cao,
Yichen Huang
et al.

Abstract: Background Traumatic brain injury (TBI) is a significant worldwide public health concern that necessitates attention. Apoptosis signal-regulating kinase 1 (ASK1), a key player in various central nervous system (CNS) diseases, has garnered interest for its potential neuroprotective effects against ischemic stroke and epilepsy when deleted. Nonetheless, the specific impact of ASK1 on TBI and its underlying mechanisms remain elusive. Notably, mutation of ATP-binding sites, such as lysine residues,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…In addition, neuroprotective medications such as ethyl pyruvate improved white matter remodelling by promoting microglial state conversion in a rat TBI model 51 . Other studies have demonstrated that alleviating endoplasmic reticulum stress and blood–brain barrier damage reduces neuroinflammation and eventually improves white matter integrity 52,53 . Furthermore, other studies revealed that microglia alleviate WMI by interacting with oligodendrocytes 54,55 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, neuroprotective medications such as ethyl pyruvate improved white matter remodelling by promoting microglial state conversion in a rat TBI model 51 . Other studies have demonstrated that alleviating endoplasmic reticulum stress and blood–brain barrier damage reduces neuroinflammation and eventually improves white matter integrity 52,53 . Furthermore, other studies revealed that microglia alleviate WMI by interacting with oligodendrocytes 54,55 .…”
Section: Discussionmentioning
confidence: 99%
“… 51 Other studies have demonstrated that alleviating endoplasmic reticulum stress and blood–brain barrier damage reduces neuroinflammation and eventually improves white matter integrity. 52 , 53 Furthermore, other studies revealed that microglia alleviate WMI by interacting with oligodendrocytes. 54 , 55 However, the exact underlying mechanisms have yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…At the core of this positive feedback loop is microglia, which can initiate inflammatory pathways following brain damage from diverse causes, impact the structure of BMECs, and disrupt the tight junctions of the blood-brain barrier through the release of inflammatory cytokines. Once the cell-cell connections of the blood-brain barrier are compromised, the infiltration of peripheral immune cells and exogenous neurotoxic substances further stimulate microglia [52,197]. This sequence of events encompasses several classic inflammatory manifestations, including the release of TNF-α, IL-6, and IL-1β, as well as the transition of microglia from the M2 to M1 phenotype [198,199].…”
Section: Cell Phenotype and Specific Structure 421 Blood-brain Barriermentioning
confidence: 99%
“…Secondly, the infiltration of the peripheral immune cell barrier into the brain can lead to damage of the original neurovascular unit (NVU) [52]. Finally, the proinflammatory phenotypic changes in microglia are also directly or indirectly associated with the infiltration of peripheral cells [197].…”
Section: Cell Phenotype and Specific Structure 421 Blood-brain Barriermentioning
confidence: 99%